2003
DOI: 10.1074/jbc.m301247200
|View full text |Cite
|
Sign up to set email alerts
|

CRIM1 Regulates the Rate of Processing and Delivery of Bone Morphogenetic Proteins to the Cell Surface

Abstract: The Crim1 gene is predicted to encode a transmembrane protein containing six von Willebrand-like cysteine-rich repeats (CRRs) similar to those in the BMPbinding antagonist Chordin (Chrd). In this study, we verify that CRIM1 is a glycosylated, Type I transmembrane protein and demonstrate that the extracellular CRR-containing domain can also be secreted, presumably via processing at the membrane. We have previously demonstrated Crim1 expression at sites consistent with an interaction with bone morphogenetic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 27 publications
2
115
0
3
Order By: Relevance
“…Importantly, it has been shown that the growth factor-binding ability of Crim1 largely resides in the CRR domains. While a deletion mutant lacking the region encoded by exon 2 but retaining the IG-FBP and CRR domains was capable of binding BMPs (Wilkinson et al, 2003), we would predict that the protein present in Crim1 KST264/KST264 mice is too short to contain a significant complement of CRR domains. As such, it may behave as an effective null.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Importantly, it has been shown that the growth factor-binding ability of Crim1 largely resides in the CRR domains. While a deletion mutant lacking the region encoded by exon 2 but retaining the IG-FBP and CRR domains was capable of binding BMPs (Wilkinson et al, 2003), we would predict that the protein present in Crim1 KST264/KST264 mice is too short to contain a significant complement of CRR domains. As such, it may behave as an effective null.…”
Section: Discussionmentioning
confidence: 89%
“…One such protein is Crim1. We have previously shown that this transmembrane protein, which also contains an insulin-like growth factor binding protein (IG-FBP) motif and six vWF-C type cysteine-rich repeats, can modulate the activity of BMPs in a cell-autonomous manner in vitro (Wilkinson et al, 2003). In this study, we have characterized the phenotype of the Crim1 KST264 gene-trap mouse strain and detailed new sites of Crim1 expression based on a ␤-Geo reporter gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations